Expanding the spectrum of white matter abnormalities in Wolfram syndrome: a retrospective review - Simo, Justin; Lugar, Heather M.; Miller, Elka; Wilf-Yarkoni, Adi; Goldberg, Yael; Kocaağa, Ayça; Ito, Shoichi; Cocozza, Sirio; Frontino, Giulio; Baldoli, Cristina; Benbachir, Aziz; Ashton, Catherine; et al. (Frontiers in Neurology, 2025)
Background and objectivesWolfram syndrome (WFS) is a genetic disorder mainly caused by pathogenic variants in the WFS1 gene. It is characterized clinically by optic atrophy (OA), diabetes mellitus (DM), sensorineural hearing loss (SNHL), diabetes insipidus (DI), and variable neurological/psychiatric symptoms. WFS typically manifests before age 20 and progresses into adulthood. Classical neuroradiological features include cerebellar and/or brainstem atrophy as well as white matter abnormalities ranging from small, ovoid lesions to diffuse, symmetrical changes along the visual pathway. Following the identification of multifocal, progressive white matter abnormalities that prompted the consideration of multiple sclerosis (MS) in two molecularly confirmed WFS subjects, we sought to verify whether MS-like lesions constitute a novel WFS-associated MRI pattern.MethodsWe conducted an international multicenter retrospective study of the clinical, genetic, and radiological data from 17 unrelated WFS subjects.ResultsSeven subjects (7/17; 41%) showed at least one focal white matter lesion evocative of MS. Among these seven, three fulfilled the McDonald radiological criteria of dissemination in space and time, suggesting an inflammatory demyelinating process. All subjects reviewed in the study had at least one of the classical WFS MRI features.ConclusionOur report expands the WFS spectrum of white matter involvement to include progressive, seemingly inflammatory demyelinating lesions. While we cannot exclude the possibility of a WFS-MS dual diagnosis in some cases, the role of WFS1 in myelination suggests a selective white matter vulnerability in WFS. Our findings suggest that follow up MRI should be recommended to adult subjects with WFS. Further identification and longitudinal study of adult WFS subjects is required to confirm whether a WFS molecular diagnosis confers susceptibility to the development of MS.